Reuse of Non-Degradable Waste Polyethylene Bottles for Ground Improvement - Murad Khan; Muhammad Haseeb Zaheer; Hamayun Khan Kakar; Zohaib Ullah; Khuda Bukhsh (Journal of ICT, Design, Engineering and Technological Science, 2023)
This paper proposes the use of waste plastic bottles as a soil stabilizer. Plastics have always been difficult to dispose of since they are non-biodegradable. Today's building industry is in desperate need of low-cost materials to improve soil strength and bearing capacity. Waste plastic can be used to improve the geotechnical qualities of poor-grade soil. One of the most prevalent problems with recycling plastic is that it is typically made up of more than one type of polymer or has fibers added to it for increased strength. To measure the impact of plastic trash, various tests such as California bearing ratio (CBR), standard proctor, specific gravity and atterberg limits were performed on various samples. The current research discusses the current state of utilization of various waste plastics for soil enhancement in terms of geotechnical parameters. Outcomes of the experimental performance indicate that plastic waste can be used for soil stabilization and to alleviate the difficulty of disposing of plastic waste as well as resolving environmental issues.